Maintenance energy requirements in cats following controlled weight loss: An observational study. (July 2021) - German, A.J.; Woods, G.R.T.; Flanagan, J.; Biourge, V.
Highlights: Maintenance energy requirement (MER) after weight loss in cats was measured. MER after weight loss was similar to energy intake at the start of weight loss. Post-weight loss MER was correlated with mean energy intake during weight loss. No other variables were associated with post-weight-loss MER. MER as fed was less than the average MER recommended for pet cats. Abstract: There is a paucity of information regarding the phenomenon of weight regain after successful weight reduction in cats. This study aimed to estimate post-weight reduction maintenance energy requirements (MER) required to maintain stable weight in a group of pet cats. Nineteen cats that had successfully completed a controlled weight reduction programme were enrolled. For inclusion, at least 2 months of follow-up had to be available for review, and the maximum change in weight during maintenance was ±2%. Post-weight-reduction MER was estimated by determining dietary energy consumption from owner diary records. The Friedman test was used to compare bodyweight and energy intake at different stages of weight management. Simple and multiple linear regression were used to identify factors associated with post-weight-reduction MER. The median (interquartile range) duration of weight maintenance was 179 days (119–408 days) and, during this time, MER was 273 ± 56.7 kJ per kg 0.67 ideal bodyweight (IBW) per day. Post-weight-reduction MER was greater than metabolisable energy intake at the end (233 ± 29.5 kJ IBW per kg 0.67 per day; P < 0.001) but not the start (255 ± 38.6 kJ per kg 0.67 IBW per day; P = 0.148) of the weight reduction period. Using simple and multiple linear regression, the only variable that was associated with post-weight reduction MER was the mean ME intake during weight reduction ( r 2 = 0.349, P = 0.008). Post-weight-reduction MER at the lower limits of MER recommendations for pet cats might predispose to weight regain during the weight maintenance phase.